Perindopril and losartan affect ACE-2 and IL-6 expression in obese rat model - Andrianto, Andrianto; Hermawan, Hanestya O.; Harsoyo, Primasitha M.; Zaini, Bagas SI.; Muhammad, Akbar R. (Narra Sains Indonesia, 2024)
Obesity has emerged as a worldwide health concern due to its increasing prevalence. Adipocytes have the ability to express angiotensin-converting enzyme 2 receptors (ACE2) and several adipocytokines. These expressions could lead to the activation of a cytokine storm, which in turn promotes the development of cardiovascular diseases. The aim of this study was to investigate the impact of perindopril and losartan exposure on the ACE2 and interleukin 6 (IL-6) levels in adipocyte cells. This study used an in vivo true experimental design utilizing a post-test-only control group. A total of 24 adult male albino rats were divided into four groups, one group served as the non-obese (negative control), while the other three groups were obese: (1) the positive control (untreated obese rats); (2) perindopril group (2 mg/kg BW/day orally for 4 weeks); and (3) losartan group (20 mg/kg BW/day for 4 weeks). Afterwards, the rats were euthanized, and the visceral fat tissue were obtained during dissection. The levels of ACE2 and IL-6 were measured using the enzyme-linked immunosorbent assay (ELISA). Losartan administration in obese rats resulted in a notable elevation in ACE2 levels compared to both the perindopril group (losartan vs perindopril, p=0.011) and the positive control (p=0.004). In addition, the treatment of perindopril and losartan in obese rats resulted in a significant reduction in IL-6 levels when compared to the positive control (perindopril vs positive control, p=0.020; losartan vs positive control, p=0.002, respectively). This study provides insight into the administration of perindopril and losartan, which could suppress the pro-inflammatory (IL-6) but increase the ACE2 levels in adipose tissue.